Role of Maternal & Fetal Factors in Relation to Low Birth Weight (Medicine Today, 2022)
Introduction: Low birth weight (LBW) continues to remain a major public health problem worldwide. There are numerous factors contributing to LBW both maternal and fetal. The mortality of low birth weight can be reduced if the risk factors are detected early and managed by simple techniques.Objective: To identify the maternal and fetal factors associated with low birth weight.Materials and Methods: This case control study was conducted in Department of Pediatrics, Khulna Medical College& Hospital from January 2019 to June 2019. After delivery of the baby weight of the newborn was measured with digital weighing scale. Mothers of babies with birth weight